Surface enhancement of metallic parts fabricated by selective laser melting - Ong, Wee Ming (Nanyang Technological University, 2024)
Selective laser melting is a 3D printing technology that works with metals and is becoming increasingly popular in the industry due to several advantages over conventional machining, including material efficiency, easier manufacturing of complex geometries and lower manpower requirements. While SLM has immense potential, it is held back because of defects inherent to the process which compromise part performance, particularly fatigue life. Shot peening is a post-processing technique that uses pellet impacts to create compressive residual stress or CRS. CRS pushes the material together, delaying crack formation and propagation, thus improving fatigue life. However, the complex interplay of variables means that the effect of shot peening parameters are difficult to extrapolate from available data. Additionally, there are few or no studies on severe shot peening for SLM Ti-6Al-4V. The objective of my project is to characterise the effect of a certain set of severe shot peening parameters (0.6mmA,90-degree impingement etc) on Titanium-64 to determine its feasibility in improving the fatigue life of SLM Ti-6Al-4V. We also look into the effect of severe shot peening on adjacent sides to determine its effect. My analysis comprises both the mechanical and microstructural areas and uses techniques such as Vicker’s hardness and multiple microscopy techniques. It was found that the severe shot peening parameter used created a deeper affected zone, increasing hardness up to a depth of around 2.3mm (2300 microns). For adjacent face peening, the location of maximum effect was located, and a depth profile taken at that distance to determine the maximum increase in hardness possible from adjacent side peening. Adjacent side peening was found to have a notable effect below 500 microns depth, but the effect was minimal after. An etch-resistant layer was also discovered, likely to be the combined effect of grain refinement and time of exposure to air. Several defects were also found from the shot peening process, such as surface/sub-surface cracks, folds and rolled edges. In one sample, cracking was so severe that a portion of the sample delaminated. In conclusion, the current severe shot peening parameters pose an appreciable risk of damaging the part and compromising structural integrity/fatigue life. Safety-wise, it is recommended that further research be conducted with less aggressive parameters.